Relationship Between Glycosylated Hemoglobin Level and Sciatic Nerve Block Performance in Diabetic Patients - (:unkn) unknown (SAGE PUBLICATIONS INC, 2013)
Background: The objective of the present study was to explore the effects of deficiencies in glucose regulation on the onset, regression, and block performance times in a group of patients with diabetes-related foot problems. Methods: Forty-eight patients with American Society of Anesthetists physical status 2-4 undergoing foot and ankle surgery with a popliteal fossa block were prospectively studied. Patients were stratified into cohorts based on 3 groups according to their HbA1c levels: group 1 (n = 15), HbA1c 5%-6%; group 2 (n = 16), HbA1c 7%-8%; group 3 (n = 17), HbA1c 9%-10%. A standardized local anesthetic mixture containing 10 mL of 2% prilocaine and 10 mL of 0.5% levobupivacaine was used in all study groups. The primary outcome of the study was the time for regression of the sensory block. Results: The onset times of sensory and motor blocks in group 3 were significantly longer than those in groups 2 and 1. Motor block regression time differed significantly between groups (P = .04), being longer in group 3 compared with group 1. In group 3, the sensory block regression time and the time of first analgesic use were significantly longer than the times in groups 1 and 2. Conclusions: We found that sensory block regression time was longer in diabetic patients with poor glycemic control than in the patients with better glycemic control. Longer block performance time, probably due to reduction in sensory and motor conduction velocity in diabetic patients with poor glycemic control, should be taken into consideration when peripheral nerve blocks are used. Level of Evidence: Level II, prospective comparative study.
Keywords: glycosylated hemoglobin level; peripheral nerve block; diabetic foot; SUBCLINICAL NEUROPATHY; MELLITUS; INJURY; COMPLICATIONS; STIMULATION; CONDUCTION; DAMAGE; RATS